Acute Complications After Adult Spinal Deformity Surgery in Patients Aged 70 Years and Older. Issue 8 (October 2016) - Lonergan, Timothy; Place, Howard; Taylor, Patrick
Abstract : Study Design/Setting: This report is a retrospective case series that examined the acute complications of patients aged 70 years and older undergoing spinal deformity surgery that required fusion of at least 6 levels. Objective: To determine the acute complications that patients in the eighth decade of their life experience after spinal reconstructive surgery, and how these complication rates compare with other patient populations undergoing similar procedures. Summary of Background Data: As the mean age of the United States population rises, more older patients with painful spinal deformities can be expected. Although there are similar studies in the literature examining acute complications of patients undergoing major spinal deformity surgery, the complication rates of this unique patient population have not been adequately studied. Methods: Twenty patients had complete medical records with at least 6 months of follow-up. All the 20 patients underwent instrumented posterior spinal fusions performed by the same surgeon. Comorbidities, weighted comorbidity index, duration, number of hospital days, estimated blood loss, intensive care unit days, American Society of Anesthesiologist score, and intraoperative and postoperative complications were recorded. Results: The mean age of our patient cohort was 76.6 years (range, 70–84 y). Patients had an average of 4 comorbidities and an American Society of Anesthesiologist score of 2.7. Although the group of patients had a large number of comorbidities, their weighted comorbidity index, according to Charlson and colleagues, was fairly low at 1.05 (range, 0–4). All of the patients were fused at least 6 levels, with the average being 10.75 (range, 6–15). Ninety-five percent of patients experienced a complication of some type. Nine major complications occurred in 7 patients. Conclusions: Spinal deformity surgery in patients at any age has associated risks. These risks are believed to increase with age and the complexity of the procedure. Our results show that, although the risks of major complications are significant, the risk is not greater than in a younger population undergoing the similar procedures. We feel that age alone should not be a contraindication for patients in their eighth decade of life who are incapacitated by their painful spinal deformity.